Smart polymer composites for wood protection - Awang Ahmad Sallehin, Awang Husaini; Ngieng, Ngui Sing; Chin, Suk Fun; Hairul Azman, Roslan; Micky, Vincent; Ho, Wei Seng (Woodhead Publishing, 2020)
Wood is a porous and fibrous structural tissue of a plant that has been ubiquitously used by humans since prehistoric times. Due to its versatility, toughness, strength, rigidity, renewability, and high strength-to-weight ratio in comparison with other materials, wood has always been and will continue to be a valuable natural biopolymer of great importance to mankind. For over 390 million years, humans have found numerous benefits from wood, including feedstock for biorefineries to produce energy, chemicals, tools, and, most importantly, as building materials for houses and all wood-based construction in a variety of ways [1]. Hardwood, for example, which is typically denser, is usually utilized for wall construction, flooring, ceilings, interior joinery, wood moldings and for the making of high-quality furniture. Softwood, on the other hand, is more commonly used for inner structures such as frames of windows and doors and many other interior furnishings. As a supportive organ of woody plants that contributes to its firm structure, timber is also used as frames to support bridges and buildings, as support in mineshafts, crossbeams on utility poles, and also in railroad ties [2]. According to the Global Forest Resources Assessment (FDA), wood being the major product of forestry has contributed to an estimated amount of USD117 billion to global gross domestic product (GDP)[3]. Globally, in 2011 alone, approximately 3 billion m3 of wood was removed from the forest for various production purposes. Despite the wide range of applicability of human-made wood when it is abundant, like most other materials, wood should not be applied without putting in proper …